Comparison between acupuncture and cognitive behavioral therapy for primary insomnia: A protocol for systematic review and network meta-analysis. Issue 21 (22nd May 2020) - Peng, Wei; Zhao, Ying; Wang, Yang; Wang, Jun; Hao, Qinghong; Tu, Yang; Zhu, Tianmin
Abstract: Background: Primary insomnia (PI) is a common disease affecting human health. As the side effects of drug therapy were revealed, people began to seek more safe and effective non-drug therapies. Cognitive behavioral therapy for insomnia (CBT-I) and acupuncture are 2 commonly used non-drug therapies. However, there are few comparative studies on the efficacy of these 2 therapies. Therefore, this study aims to compare the efficacy and safety of the 2 therapies through network meta-analysis. Methods: We will search the following electronic bibliographic databases: PubMed, EMBASE, The Cochrane Library, Web of Science, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, Chongqing VIP database, and Wanfang database. Randomized controlled trials in which the intervention was acupuncture or CBT, and in which the control group was any of the above, western medicine or blank control, would be included. The primary outcome will be the changes of the Pittsburgh Sleep Quality Index, and the additional outcomes will include the changes in Insomnia Severity Index, quality of life, clinical effective rate and adverse events. Two independent authors will screen the literature in the above database, extract data and cross-check. Heterogeneity and inconsistencies are detected before using a network meta-analysis method based on frequency analysis. The risk of bias will be assessed in accordance with the Cochrane risk of bias tool, and the strength of the recommendations will be assessed by the Grading of Recommendations Assessment, Development and Evaluation. Ethics and dissemination: This network meta-analysis will provide a reference for clinicians and PI patients to choose a more appropriate non-drug regimen among multiple kinds of acupuncture or CBT-I therapies. This review does not require ethical approval and will be reported in a peer-reviewed journal. Trial registration number: PROSPERO CRD42020155327